'Old and ill': death anxiety and coping strategies influencing health professionals' well-being and dementia care. (3rd June 2017) - McKenzie, Ellen L.; Brown, Patricia M.; Mak, Anita S.; Chamberlain, Peter
ABSTRACT: Objectives: This paper examined the psychological factors that influence the well-being of health professionals who work with people with dementia and the types of care (person-centred or task-oriented) provided to these patients. Methods: The literature was reviewed to identify the factors influencing the well-being of, and types of care provided by, health professionals working with people experiencing dementia. Results: Based on our review of the literature, we propose that approaches to care and the well-being of health professionals working with dementia patients are influenced by the characterisation of dementia as a terminal illness that typically occurs in older people. Drawing upon terror management theory, we argue that exposure to dementia patients is likely to promote awareness of one's own mortality and death-related anxiety. A theoretical model is presented which posits that health professionals working in dementia care draw on experiential avoidance to manage this anxiety. Both death anxiety, and coping strategies, such as experiential avoidance, used to manage this anxiety may influence health professionals' approaches to care of, and attitudes towards, dementia patients. We also suggest a bi-directional relationship between health professionals' approaches to care and well-being. Conclusion: Recommendations are made regarding future directions for research and implications for training of health professionals providing direct service or consultation in dementia care.